USE OF CONSTRUCTION INQUIRI LEARNING MODEL TO IMPROVE THE INTEREST OF LEARNING STUDENTS GRADE XI SMA ANGKASA 2 IN COLOID MATERIALS - Sormin, Elferida; Julianti, Krisna; Nadeak, Bernadetha; Naibaho, Lamhot (PEOPLE: International Journal of Social Sciences, 2019)
This study aims to find out (1) whether the application of guided inquiry learning model can increase the learning interest of high school students of class XI IPA Angkasa 2. (2) How much increase in student learning interest obtained through the application of guided inquiry learning model. This study uses the post-nontest, pre-nontest method. The research subjects were 32 students as the experimental group using the guided inquiry model with 24 validated questionnaire statements. Data derived from the pre-nontest and post-nontest values were analyzed using the t test with an independent sample test using the SPSS 22 for window program. The results of the normality test using the Shapiro-Wilk Pre-test test is to obtain a significance value of 0.346 which means that the data is normally distributed (significant 0.346 > α 0.05). Therefore it can be stated that the data in this study are normally distributed and fulfill the requirements of research hypothesis testing based on parametric statistics. Homogenity test obtained the value of sig = 0.281 > α with α = 0.05, the data is homogeneous. Hypothesis test results using one sample t test obtained t count = 54.069 after compared with the distribution table t at a significance level of 0.05 the price of t table = 1.998, concluded t count > t table (54.069 > 1.998) or sig 0.00.